Silencing of CD133 inhibits GLUT1‐mediated glucose transport through downregulation of the HER3/Akt/mTOR pathway in colon cancer. Issue 6 (29th November 2019) - Kim, Hyungjoo; Ju, Ji‐Hyun; Son, Seogho; Shin, Incheol
Abstract : Cluster of differentiation 133 (CD133) is a transmembrane glycoprotein that has been reported as a marker of cancer stem cells or cancer‐initiating cells in various cancers. However, its contribution to tumorigenesis and differentiation remains to be elucidated. To determine the role of CD133 in colon cancer, we silenced CD133 in human colon cancer cells. Silencing of CD133 results in decreased cell proliferation, survival, migration, invasion, and glucose transport. These effects are mediated by downregulation of the human epidermal growth factor receptor 3 (HER3)/Akt/mTOR signaling pathway, culminating in reduced expression of the glucose transporter GLUT1. We also confirm that the cellular phenotypes of CD133‐silenced cells are mediated by GLUT1 downregulation. We conclude that CD133 is a potential tumor initiator that positively regulates GLUT1 expression through modulation of HER3/Akt/mTOR signaling. Abstract :